Is Self-Reported Propensity for Everyday Illusions of Control Higher in Gamblers and Is It Associated With Gambling-Specific Erroneous Beliefs?. (January 2020) - Delfabbro, Paul; Georgiou, Neophytos; Malvaso, Catia; King, Daniel
People who engage in gambling are known to hold erroneous views about the nature of gambling. One of the most commonly observed cognitive biases is the illusion of control, where people's subjective appraisal of contingency between behavior and events is greater than the objective contingency. Such beliefs have been found to be strongest in problem gamblers and can lead to over-confidence in the ability to win money from gambling. A question, however, is whether such perceptions are (a) specific to gambling and whether gamblers display a tendency to over-estimate contingencies in everyday life and (b) if a tendency to endorse everyday illusion of control beliefs is related to specific gambling-related beliefs among those who gamble. Answers to these questions might provide insights into whether some people are potentially more vulnerable to beliefs that might have implications for gambling. An online sample of 788 adults completed a survey about simple everyday situations where people might attempt to exert control (e.g., pressing elevator buttons more often, throwing dice in games). The survey included a scale that captured everyday situations as well as established measures of illusion of control and superstition in gambling. The results showed that those who report greater control in everyday tasks scored higher on standardized measures of beliefs about chance and gambling-related cognitions relating to illusory control. Scores on both types of measures were higher in gamblers than non-gamblers. The findings suggest that gamblers may differ in how they generally perceive and respond to situations involving tasks largely dominated by chance or limited opportunities for genuine control.